1991
DOI: 10.1159/000457495
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine Methyltransferase in Humans: Development and Tissue Distribution

Abstract: Thiopurine methyltransferase (EC 2.1.1.67, TPMT) was studied with 6-mercaptopurine as substrate in the cytosolic fraction from 18 human fetal liver, 16 placental and 22 adult liver specimens. TPMT activity (pmol × min^-1 × mg^-1; mean ± SD) was 33.2 ± 15.8 (fetal liver), 19.5 ± 11.1 (placenta) and 105 ± 57.1 (adult liver). Fetal liver activity of TPMT is one third that in adult liver suggesting that this enzyme is well developed in the midgestational human fetus. The distribution of TPMT seems to be ubiquitous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Our previous work on the development of conjugation pathways in humans has shown that the activities of the cytosolic enzymes, such as acetyl transferase [7], glutathione Stransferase [8], sulphotransferase(s) [9,10] and thiopurinemethyltransferase [11], are 2-3 times lower in fetal than adult liver. In con trast, the activities of uridine diphosphate glucuronyl transferase [12,13] and thiomethyltransferase [14] are 6-108 times lower in fetal than adult liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work on the development of conjugation pathways in humans has shown that the activities of the cytosolic enzymes, such as acetyl transferase [7], glutathione Stransferase [8], sulphotransferase(s) [9,10] and thiopurinemethyltransferase [11], are 2-3 times lower in fetal than adult liver. In con trast, the activities of uridine diphosphate glucuronyl transferase [12,13] and thiomethyltransferase [14] are 6-108 times lower in fetal than adult liver.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work on conjugation path ways has shown that some cytosolic enzymes such as acetyl transferase [7], glutathione Stransferase [8], sulphotransferase [9,10] and thiopurine methyltransferase [11] are better developed in fetal life compared to the pre dominantly microsomal enzymes such as glucuronyl transferase [12,13] and thiomethyltransferase [14], In order to ascertain whether such a differential development pat tern holds true for other non-microsomal enzymes as well, we measured the rate of for mation of hippuric acid from benzoic acid, which is believed to be catalysed by a mito chondrial enzyme system, namely glycine transferase [3][4][5]15], in human fetal and adult livers and kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the developmental pattern of TMT is tissuedependent and the adult kidney seems to be an important site of méthylation. Such a consideration holds true for thiopurinemethyltransferase, the activity of which is twice as high in kidney than in liver [13].…”
Section: Mean ± Sdmentioning
confidence: 99%
“…TPMT is a cytoplasmic enzyme present in liver, kidney and brain cells, red and white blood cells and bone marrow cells that catalyses the S-methylation of 6-MP and 6-TG [Remy 1967;Weinshilboum et al, 1978;Van Loon and Weinshilboum 1982;Woodson and Weinshilboum 1983;Weinshilboum 1989;Pacifici et al, 1991;Szumlanski et al, 1992;Van Loon et al, 1992;McLeod et al, 1995;Coulthard et al, 1998] with S-adenosyl methionine (SAM) as a methyl donor [Remy 1963;Elion 1967]. Although extensively studied and present already in primitive species [Otterness et al, 1985;Salavaggione et al, 2005], the physiological role of TPMT is not clear and a defective enzyme has not been linked to any disease .…”
Section: Tpmt Pharmacogeneticsmentioning
confidence: 99%